Characteristics of ATPase activity and the subunit composition of myosin in the conduction system of bovine heart - Tamura, Yoshiyuki; Nishimoto, Tetsuo; Miyakami, Sciji; Sako, Harunobu; Saito, Ken; Mori, Hiroyoshi (FEBS Letters, 1984)
The ATPase activity, light chains and isoenzymes of myosin from specialized myocardial tissue (the A-V node, bundle of His, and right and left bundle branches) of bovine heart were compared with those of atrial and ventricular myosins. The order of Ca 2+-activated ATPase activity was atrial ⪢ specialized myocardial tissue ⪢ ventricular myosin. SDS-polyacrylamide gel electrophoresis showed that myosin from the specialized myocardial tissue contained the light chains of both atrial and ventricular myosins. On the other hand, the specialized myocardial tissue contained one V 3 isomyosin and showed no difference from ventricular myocardial tissue on pyrophosphate gel.